2013
DOI: 10.1007/s10549-013-2586-y
|View full text |Cite
|
Sign up to set email alerts
|

Plasma enterolactone and breast cancer risk in the Nurses’ Health Study II

Abstract: Background Lignans are plant-based phytoestrogens with both estrogenic and anti-estrogenic properties that may be important for breast carcinogenesis. Retrospective studies have observed decreased breast cancer risk associated with high circulating enterolactone concentrations, a biomarker of lignan intake, but results from prospective studies are conflicting. Methods To prospectively examine this association, we measured plasma enterolactone levels in 802 breast cancer cases and 802 matched controls nested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…A matched case-control study of mainly premenopausal women in the Nurses’ Health Study II cohort found no overall relationship between plasma enterolactone levels and breast cancer risk. However, in those women whose follicular circulating estradiol levels were below the median, higher enterolactone was associate with a significant decrease in breast cancer risk (OR = 0.49; 95% CI = 0.27–0.91) [ 579 ]. A meta-analysis examining the possible relationship between serum enterolactone levels and either all-cause mortality or breast-cancer associated mortality found negative correlations between the circulating lignan levels and both outcome measures (HR = 0.57; 95% CI = 0.42–0.67 for all-cause mortality and HR = 0.54; 95% CI = 0.39–0.75 for breast cancer mortality [ 580 ].…”
Section: Evidence Linking Environmental Factors and Breast Cancermentioning
confidence: 99%
“…A matched case-control study of mainly premenopausal women in the Nurses’ Health Study II cohort found no overall relationship between plasma enterolactone levels and breast cancer risk. However, in those women whose follicular circulating estradiol levels were below the median, higher enterolactone was associate with a significant decrease in breast cancer risk (OR = 0.49; 95% CI = 0.27–0.91) [ 579 ]. A meta-analysis examining the possible relationship between serum enterolactone levels and either all-cause mortality or breast-cancer associated mortality found negative correlations between the circulating lignan levels and both outcome measures (HR = 0.57; 95% CI = 0.42–0.67 for all-cause mortality and HR = 0.54; 95% CI = 0.39–0.75 for breast cancer mortality [ 580 ].…”
Section: Evidence Linking Environmental Factors and Breast Cancermentioning
confidence: 99%
“…Pinoresinol diglucoside, (+)-1-pinoresinol 4, 4′-di-O-β-D-glucopyranoside ((+)-PDG) is a glycoside lignan compound having various pharmacological functions, including antihypertension [ 1 ], [ 2 ] and prevention of osteoporosis [ 3 ]. After dietary consumption, PDG can be converted by the intestinal microflora to enterolignans [ 4 ], which can potentially reduce the risk of breast cancer [ 5 ] and other hormone-dependent cancers [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of present study is that the Danish Diet, Cancer and Health cohort may be a suitable population for research in plant lignans and enterolactone due to a large between-subject variation in plant lignan intake and circulating concentration of enterolactone compared to, for example, cohorts in the USA (38) . High quality information on outcomes and clinical information on tumour characteristics and cancer treatment was available in the present study, with the latter being rare in a cohort setting.…”
Section: Discussionmentioning
confidence: 99%